Evaluasi Kualitas Layanan IndiHome di Samarinda: Studi Kasus Berdasarkan Survei Pengunjung Samarinda Food Week - Nur Arifah, Dhini Ayu; Zaini, M. (YASIN, 2025)
Home internet usage in Samarinda continues to increase in line with growing connectivity needs, and in a competitive market context, understanding customer preferences and experiences is crucial for improving service quality, while studies on event-based assessments of home internet service quality in Samarinda remain limited. This study aims to evaluate users’ experiences with IndiHome services and to analyze the factors that influence their preferences when choosing a home internet provider. The research employed a descriptive quantitative approach with a survey design, involving 57 respondents selected through convenience sampling during the Samarinda Food Week event. Data were collected using a closed-ended questionnaire administered via Google Forms and analyzed with SPSS using Chi-square tests and binary logistic regression. The results show that the main reasons respondents choose a provider are affordable prices and network stability, while the most dominant complaint concerns unstable connections. These findings extend the literature on location-based digital service quality and provide practical input for IndiHome in formulating strategies to enhance customer satisfaction in Samarinda.